ANALYSIS OF PRODUCT DOPPLER-BROADENED PROFILES GENERATED FROM PHOTOINITIATED BIMOLECULAR REACTIONS - Aoiz, F; Brouard, M; Enriquez, P; Sayos, R (1993)
This paper, which is the companion to the experimental paper (M. Brouard, S. P. Duxon, P. A. Enriquez and J. P. Simons, J. Chem. Soc., Faraday Trans., 1993, 89, 1435) in this issue, is divided into two parts. In the first, equations for the laboratory (LAB) velocity distribution of products generated via photoionitiated bimolecular reaction are presented. These equations provide the basis for numerical simulation of these distributions from assumed forms for the centre-of-mass (CM) differential cross-section: the results may be compared directly with those derived experimentally via Fourier-transform Doppler 1 + 1 LIF or REMPI spectroscopy. The latter inversion technique is described in detail in the second part of the paper.